ANALISIS JENIS-JENIS KENAKALAN SISWA SD BAHTERA MAKMUR KECAMATAN BAGAN SINEMBAH - Siregar, Berlian Siregar Berlian; Asyari, Abu Assyari Abu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
AbstrackThis study, entitled "Analysis of Types of Elementary Students Delinquency Bahtera Makmur District of Bagan Sinembah. Of symptoms seen in elementary students Bahtera Makmur Kecamatan Bagan Sinembah problems identified in this study is an assortment of student misbehavior. The purpose of this research are: 1) Knowing overview of the types of delinquency elementary students Bahtera Makmur District of Bagan Sinembah. 2) To determine the dominant type of delinquency in SD Bahtera Makmur District of Bagan Sinembah. In this study, the authors used quantitative methods with descriptive format. The population in this study is elementary students Bahtera Makmur District of Bagan Sinembah with students numbering 86 in total consisting of three classes of fourth grade of 27 students, 35 students in grade V, and VI class of 24 students using sampling techniques saturated / total. Based on the results of data processing, it is known picture of elementary school student misbehavior Bahtera Makmur District of Bagan Sinembah, student misbehavior aspects of the environmental impact of poor communities are largely demonstrated in the category of "high" with details of delinquency as follows: a) the occurrence of fights, b) said gross , c) are not polite, d) does not have good morals, e) is always brutal, f) like to disturb the peace of others, g) gives the fray, h) the occurrence of theft. Picture of elementary school student misbehavior types Bahtera Makmur District of Bagan Sinembah which mostly shows the category of "high". So it can be concluded that the elementary student misbehavior Bagan Sinembah Bahtera Makmur District of high category, the indicators make noise while the lower category kategor low on indicators say dirty. Keywords:student misbehavior